2017
DOI: 10.4148/2378-5977.7462
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calsporin on Nursing Piglet Growth Performance and Fecal Microflora

Abstract: A total of 26 lactating sows (DNA 241, DNA Genetics, Columbus, NE) and litters were used in a discovery study to evaluate the effects of Calsporin, a direct-fed microbial containing Bacillus subtilis C-3102, on fecal microflora of nursing pigs. The treatments consisted of providing a daily oral dose of Calsporin or a placebo control to piglets during the nursing phase. Sows were randomly assigned to treatments based on farrowing date, parity, and initial BW. The treatments were applied individually to piglets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…However, some conflicting results were found by other researchers. Regarding BW, Menegat et al (2017Menegat et al ( , 2018 reported no evidence for differences between piglet diets supplemented with a commercial probiotic product (Calsporin ® : B. subtilis C-3102) and those without [5,23]. The different conclusions produced by these studies may be related to the composition of the diet, the age of the piglets, and interactions with environmental factors and dietary feed additives [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, some conflicting results were found by other researchers. Regarding BW, Menegat et al (2017Menegat et al ( , 2018 reported no evidence for differences between piglet diets supplemented with a commercial probiotic product (Calsporin ® : B. subtilis C-3102) and those without [5,23]. The different conclusions produced by these studies may be related to the composition of the diet, the age of the piglets, and interactions with environmental factors and dietary feed additives [24].…”
Section: Discussionmentioning
confidence: 99%